Kriteria Guru Ideal Perspektif kitab Ta’lim Muta’allim karya Imam Az-Zarnuji dan Relevansinya dengan Pembelajaran Abad 21 - sholikhul Huda; Ari Kusuma Dewi; Bakhrudin Al Habsyi (Ahad: Multidisciplinary Journal of Islamic Studies, 2025)
Teachers are important people in the world of education, but in the 21st century there are many cases that violate the code of ethics of a teacher. These actions are carried out by several irresponsible teachers so that the world of education experiences an ethical decline. The book of ta'lim muta'allim by Imam Az-Zarnuji describes the criteria for an ideal teacher and its relevance to learning in the 21st century. This research is a library research, data is taken from various reading sources such as books, journals and previous research. The results of this study are that the ideal teacher has 3 characteristics, namely: Alim, wara' and older. The conclusion of this study is the relevance between the content in the book of ta'lim muta'alim and the character of 21st century teachers emphasizes ethics in the learning process so that they can guide students who are moral and have good spirituality.